MEMBEDAH MUSNAD AL-HUMAYDÎ: SALAH SATU MUSNAD HADITS TERTUA - Syukron Affani (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2015)
Al-Humaydî is one of the figures of hadist from Mecca area. He belongs to the main generation as the follower of tâbi`în who lived and gathered with one of the chiefs of fiqh Madzhab, which is Muhammad bin Idris al-Syâfi’î. Thus, al-Humaydî belongs to the earliest ulama of madzhab Syâfi’î. In the knowledge of Hadist, al-Humaydî and his Musnad book becomes the part of the early musnad kitab even earlier than the most popular musnad book by Ahmad bin Hanbal. Although musnad book of al-Humaydî is not the most popular book but this book belongs to the most important musnad Hadist book. Al-Bukhârî as a popular Mukharrij takes Hadist from al-Humaydî with least corrections. Al-Humaydî is the teacher of al-Bukhârî in Hadist and also for fiqh. This proves that the figure of al-Humaydî as the reader of hadist is believable. But, not all the Hadist in the musnad al-Humaydî is shahîh/true. Some of the munqathi’ Hadist which is told by al-Humaydî and al-Bukhârî knew this. This writing is trying to partly introduce and give some notes of al-Humaydî and his musnad. Therefore we will know one of the ancient Hadist books and know the figures of the one who arrange and understand the musnad Hadist book. Kata Kunci:Al-Humaydî , Musnad, Hadits, al-Bukhârî